2022
DOI: 10.1136/bmjopen-2021-055658
|View full text |Cite
|
Sign up to set email alerts
|

Global eHealth capacity: secondary analysis of WHO data on eHealth and implications for kidney care delivery in low-resource settings

Abstract: ObjectiveTo describe the use of electronic health (eHealth) in support of health coverage for kidney care across International Society of Nephrology (ISN) regions.DesignSecondary analysis of WHO survey on eHealth as well as use of data from the World Bank, and Internet World Stats on global eHealth services.SettingA web-based survey on the use of eHealth in support of universal health coverage.Participants125 WHO member states provided response.Primary outcome measuresAvailability of eHealth services (eg, elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It is possible there has not been as many digital health interventions for chronic disease implemented in low-income countries. 57 However, we would hypothesise that the unique experiences synthesised in this review would differ from those exclusively represented in low-income countries. 58 Fourth, despite a wide variety of digital health interventions represented in our review, our results (as well as the reviews we analysed) were aggregated thematic syntheses of these, reporting perspectives on digital health tools in general.…”
Section: Discussionmentioning
confidence: 94%
“…It is possible there has not been as many digital health interventions for chronic disease implemented in low-income countries. 57 However, we would hypothesise that the unique experiences synthesised in this review would differ from those exclusively represented in low-income countries. 58 Fourth, despite a wide variety of digital health interventions represented in our review, our results (as well as the reviews we analysed) were aggregated thematic syntheses of these, reporting perspectives on digital health tools in general.…”
Section: Discussionmentioning
confidence: 94%
“…Structural barriers [106,107] to the use of telemonitoring include lack of adequate infrastructures (cellular network, WiFi connectivity), the need for simple and user-friendly devices, possibly integrated into mobile phones, tablets, or home appliances, and the need to ensure data integrity, security, and privacy. Despite the structural barriers, the use of telehealth services has significantly increased, especially during and following the COVID-19 pandemic [110,111] . Moreover, a recent study has shown increasing use of eHealth services worldwide, albeit still reduced in low-and lower-middle-income countries [112] .…”
Section: Potential Barriers To Using Telemonitoring In Ckdmentioning
confidence: 99%